Acute Abdominal Pain with Obstructing Trichobezoar: A Pediatric Case of Rapunzel Syndrome Diagnosed in a Pediatric Emergency Department - Sung-Ha Kim; Jong-In Lee; Soohyun Park; So-Hyun Paek (Pediatric Reports)
Introduction: Acute abdominal pain is a prevalent complaint in pediatric emergency departments. Primary care physicians can find it challenging to treat such pain and, in particular, to determine whether it requires emergent surgical intervention. Acute appendicitis is the most common surgical cause of abdominal pain, but it is important to understand that other rare conditions can also be life-threatening. Case presentation: We report the case of a 6-year-old girl who presented to our pediatric emergency center with complaints of acute abdominal pain, vomiting, and diarrhea. She had no notable medical history, including perinatal, surgical, or psychiatric disorders. After finding a bezoar-like structure through a combined enteritis CT scan, reassessing the child’s dietary concerns revealed that the child had experienced symptoms of trichophagia for approximately 3 to 4 years. Enterotomy and the removal of the bezoar were successfully performed. A pediatric psychiatric consultation was carried out to prevent further trichophagia-induced complications. Conclusions: Despite our patient’s relatively young age and the failure to obtain a history of trichophagia at the onset, we successfully diagnosed a rare condition called Rapunzel syndrome. Although several cases of this condition have been reported by pediatric surgeons, we emphasize the role of physicians in pediatric emergency departments when examining children with this rare syndrome.